Correlation of Uji Tahap Bersama (National Joint Exam) Results with Multiple Choice Questions (MCQ) Exam Scores in Medical Students - Hendra, Gabriel Septian; Yulistini, Yulistini; Suharti, Netti; Firdawati, Firdawati; Usman, Elly; Putri, Biomechy Oktomalio (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2024)
Background: Uji Tahap Bersama is a form of formative assessment initiated by the Association of Indonesian Medical Education Institutions (AIPKI) and the Ministry of Education and Culture (Kemendikbud) to maintain the quality of medical student learning in Indonesia. The Faculty of Medicine Universitas Andalas uses the Problem-Based Learning (PBL) method in organizing an educational system with summative assessment in the form of a computer-based Multiple-Choice Questions (MCQ) exam. Formative and summative assessment is a form of assessment that assesses the extent to which students understand the learning material that has been given. This study aims to determine the correlation between summative and formative assessment results in medical students' classes in 2017 and 2018, Faculty of Medicine, Universitas Andalas.Methods: This analytic, cross-sectional research involved 174 medical students from the Faculty of Medicine, Universitas Andalas, representing the 2017 and 2018 classes. The participants completed all pre-clinical phase blocks (except elective blocks) and took Uji Tahap Bersama I and II during their respective periods. Purposive sampling, meeting inclusion and exclusion criteria, determined the sample. The secondary data, which included the results of Uji Tahap Bersama I and II as well as MCQ scores before remedial, were analyzed through regression using the Pearson correlation test. To determine the extent to which MCQ affects the UTB outcomes, the coefficient of determination (r2) is used, which is obtained from the square of the correlation coefficient (r). The findings were interpreted based on Colton's correlation interpretation guidelines. Results: The findings revealed significant correlations in all four analyses conducted. UTB I results correlated significantly with average MCQ scores for the 1st to 4th semesters, while UTB II results correlated substantially with average MCQ block scores for the 1st to 7th semesters across batches. These correlations ranged from moderate to very strong.Conclusion: This study establishes a noteworthy correlation between UTB results and the average MCQ scores among medical students at the Faculty of Medicine, Universitas Andalas. The findings underscore the relevance of UTB as a formative assessment tool in maintaining and gauging the quality of medical education in Indonesia.